Legal Aspect on Packaging and Marketing Strategy for Traditional Salt Products in Les Village, Tejakula District, Buleleng Regency (Universitas Negeri Semarang, 2022)
The objectives of this community service activity are: 1) Making a trademark and being registered with HKI as self-identity in marketing salt products. 2) Train skills in traditional salt packaging. 3) Train skills in product marketing through market place and social media. The target audience in this service is the Tasik Segara 1 Group, Les Village. The implementing team chose the mentoring method as the method in carrying out this community service activity. The stages in the implementation of this assistance are adjusted to the issues raised and the needs of partners. The result of this activity is that partners have knowledge of trademarks and the Intellectual Property Rights registration process, and partners have trademarks related to the Les Village traditional salt processed product, namely